Evolution of water quality regulations in the United States and Florida - Kati W. Migliaccio; Yuncong Li (EDIS, 2008)
ABE-381, a 5-page illustrated fact sheet by Kati W. Migliaccio and Yuncong Li, summarizes US water quality legislative history, Florida water quality legislation, and water quality criteria development. Includes references. Published by the UF Department of Agricultural and Biological Engineering, December 2007.